2018
DOI: 10.22146/ijc.21183
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Glucose Oxidase on Modified-Carbon-Paste-Electrodes for Microfuel Cell

Abstract: ABSTRACT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…9 In recent years, the glucose measurements are based on immobilization of GOx as complicated systems for detecting H2O2 concentration which is quick and accurate. [10][11][12] Ambarsari et al 13 reported a glucose biosensor utilizing nanofiber-polyaniline/glutaraldehyde as an immobilization matrix for GOx in an enzymatic fuel cell system. GOx has been isolated from a local fungus collection of Aspergillus niger (IPBCC.08.610) with yield and activity was 72.86% and 27.77 U/mg, respectively.…”
Section: Glucose + O → H O + Gluconic Acidmentioning
confidence: 99%
See 4 more Smart Citations
“…9 In recent years, the glucose measurements are based on immobilization of GOx as complicated systems for detecting H2O2 concentration which is quick and accurate. [10][11][12] Ambarsari et al 13 reported a glucose biosensor utilizing nanofiber-polyaniline/glutaraldehyde as an immobilization matrix for GOx in an enzymatic fuel cell system. GOx has been isolated from a local fungus collection of Aspergillus niger (IPBCC.08.610) with yield and activity was 72.86% and 27.77 U/mg, respectively.…”
Section: Glucose + O → H O + Gluconic Acidmentioning
confidence: 99%
“…The modified carbon paste electrode (MCPE) was made with 2 mg nanofiber-polyaniline by thoroughly mixing in mortar 100 µL paraffin with 0.15 g of graphite powder according to method Ambarsari et al 13 with slight modification. For the preparation of MCPE capillary glass (diameter of 3 mm) the tubes were filled which carbon paste with the size of 3, 5, 7 and 10 mm.…”
Section: Preparation Of Modified Carbon Paste Electrodesmentioning
confidence: 99%
See 3 more Smart Citations